HO‐1 regulates the function of Treg: Association with the immune intolerance in vitiligo. Issue 9 (5th July 2018) - Zhang, Qian; Cui, Tingting; Chang, Yuqian; Zhang, Weigang; Li, Shuli; He, Yuanmin; Li, Bing; Liu, Ling; Wang, Gang; Gao, Tianwen; Li, Chunying; Jian, Zhe
Abstract: In vitiligo, cutaneous depigmentation is accompanied by increased T cell cytolytic activity targeting melanocytes, indicating that autoimmune tolerance is disrupted. The inhibited amount and function of Tregs have been indicated to be involved in the autoimmune intolerance in vitiligo, however, with the conclusion still controversial and the involved mechanism unknown. In this study, we explored the molecular and cellular alterations accounting for the impaired Treg response in vitiligo. Our results showed that the amount of Tregs was drastically reduced in peripheral blood of active vitiligo patients. Furthermore, the immunoregulatory function of Tregs was attenuated, with lower expression of CTLA4, IL‐10 and TGF‐β. Moreover, the expression of HO‐1, a functional modulator of Tregs, was decreased in vitiligo Tregs, and the concentrations of HO‐1 metabolites, including bilirubin, CoHb and iron, were correspondingly decreased in serum of vitiligo patients. In addition, we treated the Tregs from vitiligo patients with Hemin, an agonist of HO‐1, and found that enhanced HO‐1 expression restored the function of Tregs by up‐regulating IL‐10 expression. Our study demonstrates the essential role of HO‐1 in the impaired Treg response in vitiligo and indicates the potential of HO‐1 as a therapeutic target in vitiligo management.